Optimization of Thickness of YSZ Coating on an Aluminium Piston in I.C. Engines Using a Genetic Algorithm Approach - Shafeeq, Mohammed Abdul; Jajimoggala, Sarojini; Shabana, Shabana (Journal of bio- and tribo-corrosion, 2024)
Huge increase in the demand for better durability and efficiency in engines necessitated the usage of thermal barrier coatings on the piston which reduces the damage due to heat and increases the combustion performance of the engine. This work mainly aims on an Aluminium piston in which the crown is coated by Yttria-Stabilized Zirconia. Optimization of the thickness of the above-mentioned coating is done by using a Genetic algorithm approach. Yttria-Stabilized Zirconia (YSZ) coating has been utilized to increase the performance of combustion in the engine and to decrease the damage due to heat on the engine. Analysis was performed with the help of Finite element modelling which was implemented with the help of Abaqus Python Scripting. In this work, optimum thickness of the coating was found to be around 1.38 mm. It is also identified that there was a high increase in the temperature at the top of a coated surface of a piston when compared with the piston which has no coating. Results show that piston with YSZ coating has a temperature around 770 °C, whereas the uncoated piston is limited to temperature around 586 °C, which results in the approximate percentage increase of 32 percent. This result is of great use for the piston manufacturers in the automotive industry.